Answer:
Ok, for f(x) = x^2 we have only one x-intercept (actually, two equal x-intercepts) at x = 0.
Now, for g(x) = (x - 2)^2 - 3
First, let's analyze the transformations.
When we have g(x) = f(x - a) this means that we moved "a" units to the right (if a is positive)
When we have g(x) = f(x) + a, this means that (if a > 0) we move the graph "a" units up.
In this case we have both those transformations:
g(x) = f(x - 2) - 3
this means that we move 2 units to the right, and 3 units down (because the number is negative)
now we can find the roots of g(x) as:
g(x) = (x - 2)^2 - 3 = x^2 - 4x + 4 - 3 = x^2 - 4x + 1 = 0
using the Bhaskara's equation:
![x = (4 +-√(4^2 - 4*1*1) )/(2*1) = (4 +- 3.5)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/hrxe299zzeo4ya6cg8m1tnpo3dqk8j0628.png)
then the roots are:
x = (4 + 3.5)/2 = 3.75
x = (4 - 3.5)/2 = 0.25
Here we have two different x-intercepts